Outpatient management of adults with COVID-19. Issue 11 (November 2022) - Pullen, Richard L.
Abstract: This article discusses the outpatient management of adults with COVID-19 that reflects current evidence and best practices. Variants of concern, clinical presentation, assessment of the patient's clinical status, vaccination, medication management, and patient teaching are presented. Abstract : This article discusses the outpatient management of adults with COVID-19 that reflects current evidence and best practices. Variants of concern, clinical presentation, assessment of the patient's clinical status, vaccination, medication management, and patient teaching are presented.